2017
DOI: 10.3389/fphar.2017.00943
|View full text |Cite
|
Sign up to set email alerts
|

Sirt3 Mediates the Inhibitory Effect of Adjudin on Astrocyte Activation and Glial Scar Formation following Ischemic Stroke

Abstract: In response to stroke-induced injury, astrocytes can be activated and form a scar. Inflammation is an essential component for glial scar formation. Previous study has shown that adjudin, a potential Sirt3 activator, could attenuate lipopolysaccharide (LPS)- and stroke-induced neuroinflammation. To investigate the potential inhibitory effect and mechanism of adjudin on astrocyte activation, we used a transient middle cerebral artery occlusion (tMCAO) model with or without adjudin treatment in wild type (WT) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…SIRT3 reduced the production of superoxide dismutase and increased the migratory potential of microglia cells in vitro (Cao et al, 2019). Upregulation of SIRT3 in astrocytes also inhibited their inflammatory activation, highlighting the possibility of metabolic regulation by targeting epigenetics (Yang et al, 2017). Adjudin treatment promoted the functional recovery in ischemic mice by inhibiting the inflammatory activation of astrocytes through Sirt 3 upregulation (Yang et al, 2017).…”
Section: Modulation Of Glial Metabolism As a Therapeutic Strategymentioning
confidence: 98%
“…SIRT3 reduced the production of superoxide dismutase and increased the migratory potential of microglia cells in vitro (Cao et al, 2019). Upregulation of SIRT3 in astrocytes also inhibited their inflammatory activation, highlighting the possibility of metabolic regulation by targeting epigenetics (Yang et al, 2017). Adjudin treatment promoted the functional recovery in ischemic mice by inhibiting the inflammatory activation of astrocytes through Sirt 3 upregulation (Yang et al, 2017).…”
Section: Modulation Of Glial Metabolism As a Therapeutic Strategymentioning
confidence: 98%
“…Previously, it was reported that the SIRT3-FOXO3a signaling pathway was involved in the inhibitory effect of Adjudin on astrocyte activation. 15 Therefore, we hypothesized that this pathway also played a significant role in the anticancer effect of Adjudin on SCLC cells. In our study, FOXO3a siRNA was used to transfect cells that had already overexpressed SIRT3.…”
Section: Adjudin Upregulated Foxo3a By Activating Sirt3mentioning
confidence: 99%
“…Another report found that SIRT3 was responsible for the neuroprotective effects of ketone treatment following cerebral ischemia ( Yin et al, 2015 ). SIRT3 was found to be involved in inhibiting astrocyte activation in a mouse MCAO model which decreased glial scarring ( Yang et al, 2017 ). It has been purposed that SIRT3 activity could be regulated by mitochondrial uncoupling protein 2 (UCP2) during cerebral ischemia-reperfusion injury by increasing the available NAD+/NADH ratio ( Su et al, 2017 ).…”
Section: Sirt3 Modulation After Strokementioning
confidence: 99%